An improved LC-MS/MS method for the quantification of alverine and para hydroxy alverine in human plasma for a bioequivalence study☆ - Dhiraj M. Rathod; Keyur R. Patel; Hiren N. Mistri; Arvind G. Jangid; Pranav S. Shrivastav; Mallika Sanyal (Elsevier, 2017)
A highly sensitive and selective high performance liquid chromatography-tandem mass spectrometry method was developed and validated for the quantification of alverine (ALV) and its active metabolite, para hydroxy alverine (PHA), in human plasma. For sample preparation, solid phase extraction of analytes was performed on Phenomenex Strata-X cartridges using alverine-d5 as the internal standard. The analytes were separated on Symmetry Shield RP18 (150 mm×3.9 mm, 5 µm) column with a mobile phase consisting of acetonitrile and 10 mM ammonium formate (65:35, v/v). Detection and quantitation was done by electrospray ionization mass spectrometry in the positive mode using multiple reaction monitoring. The assay method was fully validated over the concentration range of 15.0-15,000 pg/mL for ALV and 30.0-15,000 pg/mL for PHA. The intra-day and inter-day accuracy and precision (% CV) ranged from 94.00% to 96.00% and 0.48% to 4.15% for both the analytes. The mean recovery obtained for ALV and PHA was 80.59% and 81.26%, respectively. Matrix effect, expressed as IS-normalized matrix factor ranged from 0.982 to 1.009 for both the analytes. The application of the method was demonstrated for the specific analysis of ALV and PHA for a bioequivalence study in 52 healthy subjects using 120 mg ALV capsules. The assay reproducibility was also verified by reanalysis of 175 incurred subject samples.